2013
DOI: 10.4236/jwarp.2013.511106
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Analysis of Well Water Sources in the Bambui Student Residential Area

Abstract: Majority of the population in the Bambui student residential area depend on wells as their source of water supply. Due to increasing complaints from students after using this well water sources, this study was carried out to examine the microbial quality of well water sources in the Bambui student residential area, Bamenda, Cameroon as a way of safe guarding public health against water borne diseases. Water samples from a total of fifteen wells, covered and uncovered were assessed for their bacteriological qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
4
6
1
Order By: Relevance
“…These values are high when compared with the permissible MPN index by world Health Organization of 10 coliforms/100ml of water sample. This observation is consistent with the reports of many researchers [16,27,30] who reported high coliform counts in water analyzed.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These values are high when compared with the permissible MPN index by world Health Organization of 10 coliforms/100ml of water sample. This observation is consistent with the reports of many researchers [16,27,30] who reported high coliform counts in water analyzed.…”
Section: Discussionsupporting
confidence: 94%
“…The result of the present study showed that total viable bacterial count in the drinking water samples ranged from 6.0×102 CFU/ml to 4.0×108 CFU/ml; this was high and exceeded the recommended limit of <500 CFU/ml. This result is similar to the work of Ngwa and Chrysanthus [27] and Agwaranze et al [28] who reported viable count of bacteria in the range of 2.0×103 CFU/ml to 7.3×104 CFU/ml and8.6×103 CFU/ml to 3.04×104 CFU/ml respectively. The high bacteria count is an indication that the various sources of the drinking water samples are highly contaminated which could be of public health concern.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most probable number (MPN) was the microbiological analysis that was used in this research work. Most Probable Number (MPN) is a method used to estimate the concentration of viable microorganisms in a water sample by replicating liquid broth growth in ten-fold dilutions [29][30][31][32]. Presumptive test was used for the detection and estimation of total coliform organisms; the Gram-negative bacteria that ferment lactose at 35-37ºC within 24-48 h, in the well water sample.…”
Section: Microbiological Analysis Of Well Watermentioning
confidence: 99%